The Psychometric Properties Of Students’ Attitudes, Coping Strategies, And Psychological Symptoms - Roslee Ahmad; Dede Rahmat Hidayat; Susi Fitri; Lokman Mohd Tahir; Mohd Faizal Kasmani; Rezki Perdani Sawai; Hizral Tazzif Hisham; Mohd Izwan Mahmud (INTELEKTUAL PUSTAKA, 2024)
Indexed by Scopus